Transformasi Asuransi Umum Syariah sebagai Strategi Peningkatan Kepercayaan Nasabah di Tengah Perubahan Zaman Global Modern (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the transformation of sharia general insurance as a strategic effort to enhance customer trust amid the dynamics of the modern global era, which is characterized by technological advancement, economic uncertainty, and changing consumer behavior. Global developments require sharia general insurance companies to adapt through product innovation, service digitalization, governance strengthening, and increased transparency while maintaining strict compliance with sharia principles. This research employs a qualitative approach using a literature review of relevant academic journals, industry reports, and regulatory documents published from 2020 onwards. The findings indicate that integrated transformation—particularly in the adoption of digital technology, improvement of human resource quality, and reinforcement of ethical values such as fairness, accountability, and trustworthiness—plays a crucial role in building and sustaining customer trust. Furthermore, effective communication strategies and responsive service quality significantly strengthen the relationship between sharia insurance providers and their customers. This study is expected to contribute both theoretically and practically to the development of sharia general insurance, enabling it to remain competitive and sustainable in the modern global environment.